PERAN WORLD FOOD PROGRAMME (WFP) DALAM MENANGANI KRISIS PANGAN DI SURIAH TAHUN 2018-2020 - Milandry, Amastya Fourinda; Harto, Syafri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research discusses the role of the World Food Program (WFP) in dealing with the food crisis in Syria in 2018-2020. The civil conflict that has occurred in Syria since 2011 has caused a food crisis and prolonged economic stagnation. The food crisis has entered its seventh year in 2018, which has made the situation of the Syrian population in refugee camps even more vulnerable and economic and security conditions that have not improved. This situation was exacerbated by the global Covid-19 outbreak that entered Syria in 2020 which hindered WFP from carrying out its aid program in Syria. This research aims to find out more about the role of WFP in dealing with the food crisis in Syria 2018-2020. This study uses the Theory of the Role and Function of International Organizations from Clive Archer's thought as a reference in analyzing the data obtained. This research is a descriptive qualitative research with data collection methods using library research techniques and documentary studies. The result of this research is that WFP as an international organization in dealing with the food crisis in Syria has a role as an instrument, arena and independent actor. This role can be seen in the implementation of WFP programs in Syria. The main programs of WFP are Emergency Operation (EMOP), Protracted Relief and Recovery Operation (PRRO), and Special Operation (SO). During 2018 to 2020 the role of WFP as an instrument was very visible by providing General Food Assistance (GFA) compared to other role indicators. Its role as an Arena is not very visible in 2019 and 2020 because the project that supports the role of WFP as a discussion venue, namely Livelihoods and Resilience, was not implemented according to the Strategic Plan target due to the emergence of Covid-19. Meanwhile, the role of WFP as an independent actor is only slightly visible, namely in 2020 with changes in operational procedures in carrying out its programs which must comply with health regulations in preventing the spread of Covid - 19. The role of WFP can be measured and seen from the implementation of its program in the field, depending on conditions and situations. as well as performance on the field. Keywords: Role theory, Food crisis, International Organization.